Formation of extended prismatic dislocation structures under indentation. (1st June 2016) - Gagel, J.; Weygand, D.; Gumbsch, P.
Abstract: Prismatic dislocation structures are often observed after indentation experiments. These structures usually start from the zone of high dislocation density underneath an indenter tip, but extend far beyond. Three dimensional Discrete Dislocation Dynamics simulations show how these complex structures can be formed from preexisting dislocations. The specifics of the indentation stress field and the crystallographic orientation play an important role for the formation of these structures. The mechanism of formation of the prismatic dislocations loops is dominated by stress controlled cross slip events, with cross slip locations reflecting the symmetry of the indentation stress field. Graphical abstract: